Model Analisis Kebijakan Pendidikan - Aziz, Asep Abdul; Nurfarida, Rida; Budiyanti, Nurti; Zakiah, Qiqi Yuliati (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2020)
Education was very important in human intelligence. This article aimed to describe the model of education policy analysis. This research used a qualitative approach in library studies. The results showed that the education policy model consisted of three things namely (1) formulation model, (2) analysis model, and (3) implementation model. The formulation model consists of institutional models, system models, mixed investigation models, process models, elite theory models, rational models, critical models, strategic models, deliberative models. Meanwhile, the education policy analysis model consists of a prospective, retrospective, and integrative models. The implementation model consists of top-down and bottom-up models. The results of education policy analysis used in Indonesia use more political policy analysis models based on political assumptions. Keywords: Educational Model, Policy of Educational Model, Policy Education